2016
DOI: 10.1039/c6ta03440c
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped graphene guided formation of monodisperse microspheres of LiFePO4 nanoplates as the positive electrode material of lithium-ion batteries

Abstract: Three-dimensional porous composite microspheres of LiFePO4 and nitrogen-doped graphene have been synthesized by a solvothermal process coupled with subsequent calcination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…The good electronic and ionic kinetics of LiFePO 4 @C/rGO were further supported by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) analyses (Figures S18 and S19, respectively, in the Supporting Information). The material was found to exhibit a higher rate capability than those of the LiFePO 4 /C microspherical samples reported in the literature (shown in Figure S20 in the Supporting Information) . Although the performance of LiFePO 4 @C/rGO at higher rates (>10 C) was slightly lower than that of nanosized LiFePO 4 /C reported previously, the LiFePO 4 @C/rGO material achieved a tap density of 1.3 g cm −3 , which was almost 30 % higher than that currently reported for carbon‐coated irregular LiFePO 4 nanomaterials (≤1.0 g cm −3 ), and thus, better for volumetric energy density.…”
Section: Resultsmentioning
confidence: 60%
“…The good electronic and ionic kinetics of LiFePO 4 @C/rGO were further supported by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) analyses (Figures S18 and S19, respectively, in the Supporting Information). The material was found to exhibit a higher rate capability than those of the LiFePO 4 /C microspherical samples reported in the literature (shown in Figure S20 in the Supporting Information) . Although the performance of LiFePO 4 @C/rGO at higher rates (>10 C) was slightly lower than that of nanosized LiFePO 4 /C reported previously, the LiFePO 4 @C/rGO material achieved a tap density of 1.3 g cm −3 , which was almost 30 % higher than that currently reported for carbon‐coated irregular LiFePO 4 nanomaterials (≤1.0 g cm −3 ), and thus, better for volumetric energy density.…”
Section: Resultsmentioning
confidence: 60%
“…The increase in the energy consumption and global warming has accelerated research on electrochemical energy storage devices for electric vehicles and electronic equipment [1][2][3][4][5][6]. Lithium-sulfur batteries are promising energy storage devices due to their high theoretical energy density (2600 Wh/kg) and specific capacity, natural abundance, low cost, and safety [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Rather than the planar large area foil current collectorbased electrodes used commercially, investigations of 3D electrode morphologies at the laboratory scale have also shown that faster ionic and electronic transport can be promoted, which supports faster charging and/or discharging performance. [11][12][13][14][15][16][17][18] However, these approaches are difficult to scale-up economically.…”
Section: Introductionmentioning
confidence: 99%